2017
DOI: 10.1117/1.jmi.4.3.031210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organ and effective dose when using region-of-interest attenuators in cone-beam CT and interventional fluoroscopy

Abstract: In some medical-imaging procedures using cone-beam CT (CBCT) and fluoroscopy, only the center of the field of view (FOV) may be needed to be visualized with optimal image quality. To reduce the dose to the patient while maintaining visualization of the entire FOV, a Cu attenuator with a circular aperture for the region of interest (ROI) is used. The potential organ and effective dose reductions of ROI imaging when applied to CBCT and interventional fluoroscopic procedures were determined using EGSnrc Monte Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…9, 10 The ROI attenuator was inserted at the center of the x-ray field, and the phantom was irradiated with the x-rays using the identical setup as described in section 2.3.1. The resultant dose distribution was comprised of a high dose circular region of interest and a low dose periphery due to the dose intensity attenuation by the ROI beam attenuator.…”
Section: Methodsmentioning
confidence: 99%
“…9, 10 The ROI attenuator was inserted at the center of the x-ray field, and the phantom was irradiated with the x-rays using the identical setup as described in section 2.3.1. The resultant dose distribution was comprised of a high dose circular region of interest and a low dose periphery due to the dose intensity attenuation by the ROI beam attenuator.…”
Section: Methodsmentioning
confidence: 99%
“…All parts of the tube were simulated according to the manufacturer’s specifications. 3 We used the XTUBE component module (CM) of the BEAMnrc code library to simulate the tube target, with a target material of tungsten–rhenium (WRe) and an anode angle of 11 deg. The incident electron energy was simulated using a constant potential with no ripple.…”
Section: Methodsmentioning
confidence: 99%
“…The anode bremsstrahlung cross-section enhancement was increased by a factor equal to 200. 3 In all simulations, the photon energy cut-off (global PCUT) was set to 10 keV for range rejection. 4 Material data were generated by the PEGS4 code developed at the National Research Council.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, flat‐panel detectors have been developed and used as alternatives due to their significantly higher contrast and spatial resolution 62,63 . As for the radiation dose, Xiong et al 64 demonstrated the efficacy of region of interest (ROI) imaging using an ROI attenuator composed of 0.7‐mm‐thick Cu in reducing the patient radiation dose in CBCT. Compared to standard neuro‐CBCT scans without the ROI attenuator, the dose for most organs was reduced by 45%–50%, with an effective dose of approximately 46%.…”
Section: Cbct Perfusion Techniquementioning
confidence: 99%